Analisis Historis Terhadap Waqaf Ibtida Mushaf Kudus dan Mushaf Standar Indonesia - Salsabila Shofa Daniya (Mafatih, 2026)
The Mushafs circulating in Indonesia have differences, one of which is the difference in waqaf and ibtida. Since the beginning of the writing of the waqaf and ibtida books, there have been many differences. This is the result of the opinions of the scholars. On the other hand, due to the differences in waqaf and ibtida, there are also differences in reading methods and tajwid rules that must be applied. These differences cause people to stop and start at different places. On the other hand, this makes it easier for people to read the Qur'an, especially those with short breath. This study uses library research through qualitative methods. From the old Kudus Quran that has been corrected, the new Kudus Quran that refers to the Medina Quran, and the Indonesian standard Quran as a standardization of Indonesian Qurans, they have different forms and places of waqaf. Focusing on Surah al-Baqarah verses 1-29. The influence of this research on the practice of reading and memorizing the Quran is to understand the history of the Kudus Quran, the Indonesian standard Quran, and the creation of the waqaf signs used in these Qurans. Mushaf yang beredar di Indonesia memiliki perbedaan, salah satunya perbedaannya pada waqaf dan ibtida. Sejak awal ditulisnya kitab-kitab waqaf dan ibtida sudah banyak perbedaan. Hal ini merupakan hasil dari pendapat-pendapat para ulama. Di sisi lain akibat dari perbedaan waqaf dan ibtida muncul juga cara membaca maupun hukum tajwid yang harus di keluarkan. Perbedaan ini menjadikan orang-orang berbeda tempat berhenti maupun tempat mengawalinya. Di sisi lain ini memudahkan orang-orang untuk membaca al-Qur’an terutama yang memiliki nafas yang pendek. Penelitian ini menggunakan penelitian library research melalui metode kualitatif. Dari mushaf Kudus lama yang sudah di tashih, mushaf Kudus baru yang mengacu pada mushaf Madinah, mushaf standar Indonesi sebagai penyeragaman mushaf-mushaf Indonesia memiliki bentuk dan tempat waqaf yang berbeda. Berfokus pada surat al-Baqarah ayat 1-29. Pengaruh penelitian ini pada praktik membaca maupun menghafal al-Quran dengan memahami sejarah mushaf Kudus, mushaf standar Indonesia, hingga terciptalah tanda waqaf yang digunakan pada mushaf-mushaf tersebut.